(untitled) (Simbiótica. Revista Eletrônica, 2025)
This review examines the recent French publication of Karl Mannheim’s 1930 general sociology course, translated and introduced by Dominique Linhardt. The ten lectures provide a unique window into Mannheim’s pedagogical method and the emergence of sociological reflexivity during the crisis of the Weimar Republic. The review reconstructs Mannheim’s analysis of the socio-historical conditions that gave rise to modern reflexivity, the role of class differences in shaping worldviews, and the development of the sociology of knowledge as a critical response to increasing social differentiation and the collapse of unified meaning. I argue that the contemporary relevance of the course lies in Mannheim’s ability to combine criticism, historicization and openness to complexity, offering a conceptual framework to understand both the contemporary resurgence of regressive attitudes and the paradoxes of what I call reflexive post-modernity